2016
DOI: 10.1111/jcpp.12598
|View full text |Cite
|
Sign up to set email alerts
|

Late childhood interpersonal callousness and conduct problem trajectories interact to predict adult psychopathy

Abstract: Background Studies have demonstrated a robust association between interpersonal callousness (IC) and the development of severe and chronic conduct problems (CP) in youth. Although children exhibiting IC are also believed to be at particularly high risk for developing psychopathic personality features in adulthood, there is little longitudinal evidence supporting this assumption, particularly after controlling for co-occuring CP severity. Methods This study used data collected on a longitudinal cohort of boys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 44 publications
0
21
0
Order By: Relevance
“…In contrast, studies of children and adolescents have often isolated specific components as key developmental markers of adult psychopathy, with a large focus on callous-unemotional traits (CU traits; Frick et al, 2014). Although a large amount of research has shown that CU traits predict more severe and stable antisocial behavior, including later psychopathic traits, CU traits may not specifically predict the interpersonal-affective components of psychopathy, which contain callousness (e.g., Burke, Loeber, & Lahey, 2007; Hawes, Byrd, Waller, Lynam, & Pardini, 2017; Lynam, Caspi, Moffitt, Loeber, & Stouthamer-Loeber, 2007). Moreover, significant heterogeneity between-individuals for both initial levels and rates of change in CU traits across development have been noted (e.g., Baskin-Sommers, Waller, Fish, & Hyde, 2015; Hawes et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, studies of children and adolescents have often isolated specific components as key developmental markers of adult psychopathy, with a large focus on callous-unemotional traits (CU traits; Frick et al, 2014). Although a large amount of research has shown that CU traits predict more severe and stable antisocial behavior, including later psychopathic traits, CU traits may not specifically predict the interpersonal-affective components of psychopathy, which contain callousness (e.g., Burke, Loeber, & Lahey, 2007; Hawes, Byrd, Waller, Lynam, & Pardini, 2017; Lynam, Caspi, Moffitt, Loeber, & Stouthamer-Loeber, 2007). Moreover, significant heterogeneity between-individuals for both initial levels and rates of change in CU traits across development have been noted (e.g., Baskin-Sommers, Waller, Fish, & Hyde, 2015; Hawes et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the cross-sectional nature of the current study did not allow for an examination of the stability of the features assessed by these measures over time. This is notable in light of concerns that have been raised regarding the downward extension of the construct of adult psychopathy to youth (see, for example, Salekin, Rosenbaum, Lee, & Lester, 2009), particularly as findings from several recent studies provide evidence of malleability among these features across development (Fontaine, Rijsdijk, McCrory, & Viding, 2010; Hawes, Byrd, Waller, Lynam, & Pardini, 2017; Hawes, Mulvey, Schubert, & Pardini, 2014).…”
Section: Discussionmentioning
confidence: 98%
“…Regarding other predictors of distal outcomes, we found that the presence of a CD diagnosis in childhood predicted its presence in adolescence, even in a model in which CU traits changes are taken into account, also supporting the chronic nature of the disorder. Previous findings 15 highlighted the importance of developing targeted interventions for children with early-onset CD, as it seems to promote the maintenance of higher levels of CU traits and more severe form of conduct problems into adolescence. Furthermore, higher levels of negative parenting in childhood are associated with a risk of substance use into adolescence, as already suggested.…”
Section: Discussionmentioning
confidence: 99%
“…Salihovic et al 14 explored the stability of psychopathic traits (including CU traits) in a sample of low-risk adolescents, and found that adolescents with persisting high levels of CU traits also maintained the highest levels of delinquency. Recently, Hawes et al 15 collected parents’ and teachers’ reported data on a cohort of boys with an oversampling of youth exhibiting elevated conduct problems. Their data suggested that, in a sample of high-risk children, the levels of CU traits predicted the development of the interpersonal/affective features of adult psychopathy.…”
Section: Introductionmentioning
confidence: 99%